Crisis upon Crisis: Refugees and COVID-19 - Ergin, Hakan (International Higher Education, 2020)
COVID-19 is an unprecedented test on higher education. What is unchanged, though, is that refugee students remain victims. Their disadvantages are health related, financial, and academic, making them more vulnerable to the pandemic than other students. It is aggravating that this virus has been associated with “otherness.” Nationalists and populists point at refugees as scapegoats spreading the disease. This adds to the hardship that they are currently suffering and, post-COVID-19, will linger as a threat.